SOSIOLOGI TUBUH DAN BUSANA MUSLIMAH - Maftuhin, Arif (Sunan Kalijaga State Islamic University & The Asia Foundation, 2017)
This paper aims at exploring sociological theories of body as an alternative approach for developing interdisciplinary Islamic studies. Three importants poinst are made trough reviewing relevant theories and literatures. First, it offers understanding of the new development in sociological theories of the body. Second, it gives emphasize on, and elaborates, the theory of docail body, which was initially developed by Michel Foucault. Third, it will analyze the Panduan Busana Muslimah book as a sample of how to use the theory of body to study one of the most prominent Islamic symbols of Islamic revivalism, the jilbab.[Artikel ini bertujuan untuk menawarkan teori tubuh sebagai salah satu alternatif pendekatan dalam kajian Islam interdisiplin, yang sering kita sebut sebagai pendekatan integrasi-interkoneksi. Untuk mencapai hal dimaksud, tiga aspek akan dibahas secara mendalam. Pertama, makalah ini menjelaskan teori-teori baru yang berkembang dalam sosiologi tubuh. Kedua, makalah ini menekankan pentingnya teori docail body yang digagas oleh Michel Foucault. Dan ketiga, makalah ini memberikan contoh aplikasi singkat bagaimana teori tubuh itu dapat digunakan untuk menganalisis salah satu fenomena revivalisme Islam.]